Abrasion Resistance and Mechanism Analysis of Polyethylene Fiber-reinforced Cementitious Composite - ZI Jinjia; LI Weibin; WANG Jihong; WANG Zhiwen; LIU Yunjun; NONG Qingshun; LI Bixiong (工程科学与技术, 2025)
ObjectiveIn hydraulic structures of the Qinghai–Xizang Plateau region, abrasion damage caused by sediment-laden water flows severely undermines the durability of hydraulic spillways, posing a significant challenge to the long - term stability and functionality of water conservancy infrastructure. Although previous studies have explored methods to enhance the abrasion resistance of concrete, the specific influence mechanism of fibers on the mechanical properties, abrasion resistance remains unclear. This study develops a high-performance anti-abrasion polyethylene (PE) fiber-reinforced cementitious material (FCM). This study aims to systematically investigate the effects of PE fiber content on the workability, mechanical properties and abrasion resistance of FCM, determine the optimal fiber content range, and reveal the underlying mechanism of PE fibers in improving the abrasion resistance of materials.MethodsThe FCM was prepared using P·O 52.5 cement, tuff powder, silica fume, manufactured sand, PE fibers, water-reducing agent, and defoaming agent. PE fibers with volume contents of 0, 0.5%, 1.0%, 1.5%, and 2.0% were added to the base mixture to prepare specimens for testing. The workability of FCM was evaluated by measuring the fluidity after vibration on a jumping table. Mechanical properties were tested, including compressive and flexural strengths. The abrasion resistance was measured using the underwater steel ball method specified in SL/T 352-2020 with a HKCM-2 concrete abrasion apparatus. The point cloud data of the damaged surface was collected by a 3D laser scanner, and the average wear depth was calculated based on this data. Scanning electron microscope (SEM) was used to observe the microstructure of FCM. Mercury intrusion porosimetry (MIP) was applied to analyze the pore structure of FCM.Results and DiscussionsThe experimental results showed that the fluidity of the mortar decreased significantly with the increase in PE fiber content. When the fiber content increased from 0.5% to 2.0%, the fluidity dropped from 285 mm to 160 mm. Regarding mechanical properties, the compressive strength of FCM first increased and then decreased with the increase in fiber content. The maximum compressive strength of 96.3 MPa was achieved at a fiber content of 1.0%. The flexural strength increased remarkably, especially when the fiber content exceeded 1.0%, with the PE2.0 group showing a 106.5% increase compared to the non-fiber group (i.e., 32.0 MPa). In terms of abrasion resistance, the inclusion of PE fibers effectively reduced the mass loss, wear rate, and average abrasion depth of the specimens. After 72 h of abrasion, compared with the non-fiber group, the mass loss of the specimens with 0.5% and 1.0% PE fiber contents decreased by 51.8% and 69.9%, respectively, and the wear rates decreased by 50.3% and 68.9%, respectively. Compared with the PE0.0 group, the maximum wear depths of the PE0.5 and PE1.0 groups were reduced by 44.6% and 24.9%, respectively. In contrast, the maximum wear depths of the PE1.5 and PE2.0 groups increased by 11.8% and 33.8% compared with the PE0.0 group. The abrasion resistance increased initially and then decreased, reaching the highest value of 159.97 <alternatives>h⋅m2⋅kg-1 <?fx-imagestate width="12.95400047" height="2.87866688"?> <?fx-imagestate width="12.95400047" height="2.87866688"?> </alternatives> at a fiber content of 1.0%, which was 232.3% higher than that of the PE0.0 group. However, when the fiber content exceeded 1.0%, the addition of fibers led to a deterioration of the interfacial transition zone (ITZ) and an increase in porosity, reducing the abrasion resistance. SEM observations revealed that the fiber-matrix interface introduced by fiber incorporation is conducive to preventing the initiation and propagation of cracks. PE fibers formed a three-dimensional network structure in the matrix, enhancing the crack-bridging ability. However, the increase in fiber content led to the degradation of the interfacial bonding performance between aggregate and cement paste. MIP analysis showed that the porosity of the matrix increased with the increase in fiber content, and the pore distribution of the matrix was deteriorated, which affected the abrasion resistance of the material.ConclusionsWhen the fiber content increased from 0.5% to 2.0%, the flowability decreased from 285 mm to 160 mm. To achieve better workability, the PE fiber content should not exceed 1.5%. Mechanical test results showed that adding 0.5%~2.0% PE fibers increased the compressive strength of fiber-reinforced cement-based composites by 8.2%~11.6% and the flexural strength by 4.5%~106.5%. PE fibers significantly enhanced the abrasion resistance of cement-based composites. After incorporating 0.5%~2.0% PE fibers, the mass loss after 72 h of abrasion decreased by 34.4%~69.9%, the abrasion rate decreased by 33.0%~68.9%, the average wear depth decreased by 23.6%~60.1%, and the abrasion strength increased by 52.5%~232.3%. The test results indicated that when the PE fiber content was 1.0%, the fiber-reinforced cement-based composites had the best abrasion resistance, with an abrasion resistance of 159.97<alternatives>h⋅m2⋅kg-1 <?fx-imagestate width="12.95400047" height="2.87866688"?> <?fx-imagestate width="12.95400047" height="2.87866688"?> </alternatives>. PE fibers exerted multiple effects on the abrasion resistance of cement-based materials. Firstly, they restricted crack propagation and aggregate spalling through the bridging effect. Secondly, they formed a three-dimensional network structure in the matrix, absorbing and dissipating energy through fiber plastic deformation. Finally, PE fibers introduced an interfacial transition zone with the matrix, enhancing the performance of weak regions in the cement-based material and thus improving the abrasion resistance. However, the incorporation of fibers also increases the porosity of the matrix and deteriorates the pore structure of the matrix. The findings of this study provide valuable insights for the application of fiber-reinforced cementitious composites in hydraulic engineering in extreme environments.